Characterization of nanostructured zinc oxide thin films synthesized at room temperature using low energy plasma focus device. Issue 10 (December 2015) - Hosseinnejad, Mohammad Taghi; Shirazi, Marzieh; Ghoranneviss, Mahmood; Hantehzadeh, Mohammad Reza; Darabi, Elham
Abstract: Nanocrystalline zinc oxide (ZnO) thin films were synthesized on glass substrates under extremely non-equilibrium conditions of energetic ion condensation during the focus phase in a low energy plasma focus (PF) device. The samples were deposited using multiple focus shots (5, 10 and 20), at constant axial and angular positions with respect to the tip of anode and anode axis (8 cm and 0°), respectively. The argon:oxygen admixture (in 7:3 ratio) was used as a working gas. The structural, morphological, electrical and optical properties of the ZnO deposited thin films were investigated. The results obtained from XRD and SEM analyzes indicated that the size of nanoparticles/agglomerates and the thickness of the ZnO thin films strongly depend on number of shots. AFM analysis revealed that the size of grains and surface roughness of ZnO samples increase with the number of shots. Measurement of the electrical parameters indicated that electrical resistivity is reduced and carrier mobility enhanced with increasing the shots, with no noticeable variations in the carrier concentration. Moreover, the results from optical transmission patterns revealed that optical transmittance and band gap energy decrease with more shots.